A CLINICAL CASE OF EMBRYONIC CANCER IN A TEENAGE GIRL - Апыхтина, Наталья Анатольевна; Елгина, Светлана Ивановна; Ламонова, Светлана Сергеевна; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Mother and Baby in Kuzbass, 2025)
Malignant neoplasms of the ovaries in children and adolescents are quite rare and have a rather aggressive course with untimely diagnosis and treatment. In many patients with diagnosed malignant ovarian tumors, the disease was detected at rather late stages due to the lack of effective screening and the erasure and/or non-specificity of the detected symptoms. Ovarian neoplasms are most often found at puberty (10-14 years), which falls during the period of changes in hormonal activity of the ovaries and gonadotropic stimulation, which is not always adequate. This article presents a clinical case of embryonic cancer in a 17-year-old girl.
Keywords: ovarian neoplasms; ovarian cancer; clinic; diagnosis; treatment; girl